Art Therapy and Speech Pathologist Language in The Empowerment of Communication Skills In Young People with Intellectual Disabilities - Rocío Molina Bejar; María Paula Vargas Mosquera (Arteterapia)
Researchwork whose aim was to explore the mode of artistic endeavors as a new intervention strategy that can be used in enhancing the speech pathologist language and stimulation of those language skills that are diminished or absent in people with intellectual disabilities. Given that people with this diagnosis have difficulty in the acquisition, development, consolidation and use of verbal and non-verbal language, thus presenting problems in the performance of school, work, social activities and even activities of daily life and symbolize course in the world.